2016
DOI: 10.1017/jmo.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and information transparency in Taiwan’s public firms: The moderating effect of family ownership

Abstract: This study incorporates insights from both institutional and family socioemotional wealth perspectives with agency theory to examine the relationships among governance practices, family ownership, and information disclosure quality. Employing a sample of 516 publicly listed firms in Taiwan over a period of 5 years (2006)(2007)(2008)(2009)(2010), we found that high levels of board independence and board activity have a significant positive effect on disclosure quality. Further, family ownership positively moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 111 publications
(141 reference statements)
0
30
0
5
Order By: Relevance
“…Umpteen studies have been conducted in recent times focusing on measuring the association between corporate governance and voluntary disclosure. Studies like Al Markati and Hamdan (2017) in Bahrain, Akhtaruddin et al (2009) in Malaysia, Al-Janadi and Rahman 2013in Saudi Arabia, Adelopo (2011) in Nigeria, Elfeky (2017) in Egypt, Li andQi (2008) China, Donnelly andMulcahy (2008) in Ireland, Eng and Mak (2003) in Singapore, Al-Shammari and Al-Sultan (2010) in Kuwait, Rouf (2011) in Bangladesh, Kent (2008) in Australia, Liu, Valenti and Chen (2016) in Taiwan, Agyei and Gyamerah (2016); Bokpin and Issahaq (2009) both in Ghana all examined corporate governance mechanism that influences the level of voluntary disclosure.…”
Section: Corporate Governance and Disclosurementioning
confidence: 99%
“…Umpteen studies have been conducted in recent times focusing on measuring the association between corporate governance and voluntary disclosure. Studies like Al Markati and Hamdan (2017) in Bahrain, Akhtaruddin et al (2009) in Malaysia, Al-Janadi and Rahman 2013in Saudi Arabia, Adelopo (2011) in Nigeria, Elfeky (2017) in Egypt, Li andQi (2008) China, Donnelly andMulcahy (2008) in Ireland, Eng and Mak (2003) in Singapore, Al-Shammari and Al-Sultan (2010) in Kuwait, Rouf (2011) in Bangladesh, Kent (2008) in Australia, Liu, Valenti and Chen (2016) in Taiwan, Agyei and Gyamerah (2016); Bokpin and Issahaq (2009) both in Ghana all examined corporate governance mechanism that influences the level of voluntary disclosure.…”
Section: Corporate Governance and Disclosurementioning
confidence: 99%
“…Consequently, it constitutes a key mechanism for aligning interests between shareholders and managers, by reducing information asymmetries and improving the quality of financial information (Callao-Gastón et al, 2008;Monterrey-Mayoral & Sánchez-Segura, 2008;Torchia & Calabrò, 2016). To complement these studies, and considering that family governance differs from non-family firms' governance (Aguilera & Crespi-Cladera, 2012;Jaggi et al, 2009;Liu et al, 2016), we first analyse to what extent accounting information is influenced by CEO non-duality. CEO non-duality consists of separating the CEO's responsibility for strategic functions from those of the board of directors.…”
Section: Quality Of Financial Information and Corporate Governancementioning
confidence: 99%
“…However, as a consequence of their long-term orientation (Lumpkin et al, 2010), family firms are more sensitive to image problems and the need to convey an environment of trust and transparency in outside financial reporting. This concern for reputation may influence family firms to adopt singular governance practices and to present higher quality financial information (Liu et al, 2016). These inconsistencies in the corporate governance of family firms constitute the second research gap identified.…”
Section: Introductionmentioning
confidence: 99%
“…The BoDs of non-listed family SMEs are less regulated and more informal than those of publicly-held family firms. Some scholars highlight that many family SMEs only have a BoDs 'on paper' and do not use it to its full extent [7]. Hence, we know little about the antecedents of BoDs effectiveness and its influence on the sustainable performance of family SMEs.…”
Section: Introductionmentioning
confidence: 99%